2012
DOI: 10.3103/s0095452712050088
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tyrosine kinase and phosphatase inhibitors on mitosis progression in synchronized tobacco BY-2 cells

Abstract: To test whether reversible tubulin phosphorylation plays any role in the process of plant mitosis the effects of inhibitors of tyrosine kinases, herbimycin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…3a ) is known as an inhibitor of mammalian PTKs 15 , the target of GNS in plants is unknown. Furthermore, several studies have shown that Tyr residues of beta-tubulins are phosphorylated in plants 28 , and GNS and Tyr-phosphatase inhibitors affect microtubule organization 29 , 30 . In our previous study, we reported that Tyr residues of beta-tubulin 2 and 7 were phosphorylated by CRK2 and CRK3 in plants 22 .…”
Section: Resultsmentioning
confidence: 99%
“…3a ) is known as an inhibitor of mammalian PTKs 15 , the target of GNS in plants is unknown. Furthermore, several studies have shown that Tyr residues of beta-tubulins are phosphorylated in plants 28 , and GNS and Tyr-phosphatase inhibitors affect microtubule organization 29 , 30 . In our previous study, we reported that Tyr residues of beta-tubulin 2 and 7 were phosphorylated by CRK2 and CRK3 in plants 22 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, meta-analysis of phosphoproteomic data revealed that Tyr-phosphorylated peptides are overrepresented in mitochondrial and characterized two Tyr phosphorylation motifs (6). Other studies have demonstrated that PTK and PTP inhibitor application to plants alter abscisic acid (8), gibberellin (9), cold stress (10), and sugar responses (11), as well as cytoskeleton organization (12) and cell division (13). These findings strongly suggest that plants possess Tyr phosphorylation signaling pathways.…”
Section: Tyrmentioning
confidence: 88%
“…Our results strongly suggest that CRKs are the responsible kinases for the Tyr phosphorylation of TBBs. Pharmacological approaches showed that PTK and PTP inhibitors can alter the stability and orientation of the microtubules (MTs) (12,13). In mammals, membrane-associated TBBs were phosphorylated by membrane-associated pp60c-src in nerve growth cones membranes (53).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that tubulin phosphorylation detected herein, corresponds to Thr-349 as previously reported (Ban et al, 2013 ). However, α-tubulin might be also targeted for Tyr phosphorylation regulating microtubule sensitivity to low temperatures (Sheremet et al, 2012a ), growth and morphogenesis of Arabidopsis root cells (Yemets et al, 2008 ) and mitotic progression in dividing tobacco BY-2 suspension culture cells (Sheremet et al, 2012b ). Although, the identity of phosphorylated residues in tubulin (and any other protein) cannot be revealed by Phos-Tag™, the method can be readily combined with immunoprecipitation of the protein of interest and subsequent probing of the resulting western blot with phospho-amino acid specific antibodies.…”
Section: Importance Of Post-electrophoretic Processing Of the Gelmentioning
confidence: 99%